The effect of self-presentation strategies in Instagram on Generation Z’s individual desired impression - Azharuddin, Aliah Amira; Wan Ahmad Kamil, Wan Nur Ain Fatimah (Journal of Islamic, Social, Economics and Development, 2025)
Instagram has helped its users to create their own personality be it according to their own style, interest, and passion, or it could be according to the audience’s preferences. According to Erin E. (2021), in social media, it is important to carefully select a friends’ list that able to accept the user’s self-presentation content and posts as the feedback given would bring effectiveness to the user’s self-presentation for future references. Hence, this study explores the effects of self-presentation strategies on Generation Z’s desired impressions through Instagram usage. Based on Goffman’s Self-Presentation Theory, it examines five strategies: ingratiation, self-promotion, exemplification, intimidation, and supplication. Using a purposive sampling method used in quantitative research where a method of sampling is mainly focuses based specific group and criterion which Instagram users among Generation Z in Klang Valley. Findings indicate that self-promotion and exemplification significantly influence desired impressions, emphasizing Generation Z’s tendency to showcase competence and moral integrity online. In contrast, ingratiation, intimidation, and supplication have a minimal impact, suggesting a shift away from passive or manipulative strategies. The study highlights the need for greater awareness of online identity construction among Generation Z. Future research should explore self-presentation across diverse platforms and cultural contexts to deepen understanding of social media’s evolving role in identity formation